Leptin Modulates the mRNA Expression of Follicle Development Markers in Post-hatch Chicks in an Age-Dependent Manner - Shaikat, Amir Hossan; Ochiai, Masami; Sasaki, Akari; Takeda, Misa; Arima, Akari; Ohkubo, Takeshi (Frontiers in Physiology, 2021)
Leptin is involved in regulating reproductive function in chickens, and the development of the leptin system is initiated during the early embryonic stage; however, whether leptin has a specific role in regulating the ovarian development in early post-hatch days is still not fully understood. This study investigated the expression of ovarian functional markers in growing juvenile chickens, along with the effects of leptin on gene expression in the hypothalamus–pituitary–gonadal (HPG) axis on specific ovarian-remodeling days. Leptin receptor (LEPR), follicle-stimulating hormone receptor (FSHR), and the mRNA expression of aromatase (CYP19A1) tended to increase with age in the ovaries of growing chicks. In the ovaries of 7-day-old chicks, intraperitoneally injected leptin significantly increased the mRNA expressions of LEPR, FSHR, and CYP19A1, and this resulted in the increased serum estradiol levels. However, leptin had no effect on hypothalamic LEPR, gonadotropin-releasing hormone 1 (GnRH1), or gonadotropin-inhibitory hormone (GnIH) mRNAs; however, in the pituitary gland, leptin significantly increased the mRNA expression of luteinizing hormone beta subunit (LHB) but had no effect on the mRNA expression of follicle-stimulating hormone beta subunit (FSHB). In 28-day-old chicks, hypothalamic and pituitary mRNAs were unaffected by leptin administration, except hypothalamic LEPR mRNA that was upregulated by a high dose of leptin. In the ovary, leptin dose-dependently decreased the mRNA expression of LEPR; low doses of leptin significantly increased the mRNA expression of FSHR, whereas high doses significantly decreased this expression; leptin did not affect the mRNA expression of CYP19A1; and high leptin doses significantly reduced the serum estradiol levels. Collectively, the results of this study show that leptin modulates ovarian development and folliculogenesis marker genes by primarily acting on ovaries on the specific ovarian-remodeling days in post-hatch chicks, which may alter folliculogenesis and ovarian development toward puberty in chicken.